2009
DOI: 10.1063/1.3250170
|View full text |Cite
|
Sign up to set email alerts
|

Dual nonlinear dielectric resonance and nesting microwave absorption peaks of hollow cobalt nanochains composites with negative permeability

Abstract: The permittivity and permeability behaviors of the hollow cobalt nanochains composites have been investigated in 2–18 GHz. The permittivity presents two dielectric resonance peaks at about 12.3 and 14.5 GHz, respectively, which mainly results from the cooperative consequence of the hollow structure and the one-dimensional structure of the as-synthesized Co nanochains. The negative permeability behavior within 12.3–18 GHz is attributed to radiation of the magnetic energy according to the as-established equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
150
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(164 citation statements)
references
References 33 publications
11
150
3
Order By: Relevance
“…The second resonance peak at 11.2 GHz is close to the resonance frequency reported in Ref. [13]. The third peak at 14.96 GHz is consistent with the resonance frequencies reported in hollow cobalt nanochains [13] and carbon-coated Sn nanorods [14].…”
Section: Methodssupporting
confidence: 86%
“…The second resonance peak at 11.2 GHz is close to the resonance frequency reported in Ref. [13]. The third peak at 14.96 GHz is consistent with the resonance frequencies reported in hollow cobalt nanochains [13] and carbon-coated Sn nanorods [14].…”
Section: Methodssupporting
confidence: 86%
“…Figure 4(a) shows the RL of the MWCNT/para±n, TiO 2 /para±n and TiO 2 @MWCNT/para±n. Generally, the RL for bare MWCNT is relatively strong in X band 17 (8)(9)(10)(11)(12) and Ku band 18 (12)(13)(14)(15)(16)(17)(18), similar phenomenon has been reported by Kshirsagar and Sharon et al 19 A strong peak can be observed at about 12 GHz and a relatively strong absorption can be observed throughout the Ku band. Besides, the RL for bare TiO 2 is weak throughout the whole frequency range, even the peak value at 15 GHz is less around À7.5 dB.…”
Section: -3supporting
confidence: 62%
“…3) is put forward to simulate this process. 14 It is found in Fig. 3(d) that the curve of " 00 versus " 0 exhibits a dielectric cole-cole semicircle plot.…”
Section: -3mentioning
confidence: 90%
“…[3][4][5][6][7][8] Nobody can give a convincing interpretation for the negative l 00 , Deng and Han 3 explain the phenomenon as the magnetic energy being radiated out, Chiu et al 7 point out it is meaningless and might be due to noise, while Chen et al 8 point out it does not arise from test error and needs further study. The electromagnetic parameters are determined via HP-5783E vector network analyzer, a sample containing 60 wt.…”
mentioning
confidence: 99%
“…Watts et al 12 have reported that defects can act as polarized centers, so the defects and groups may result in relaxation under alternated field. Most published papers present the absorption at 2 mm or near to 2 mm, [3][4][5][6][7][8][9][10] therefore, we only give the absorption of r-GO at 2 mm in Ref. 1 just for the convenience of comparison.…”
mentioning
confidence: 99%